2015
DOI: 10.1007/s10342-015-0929-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between soil bacteria substrate utilisation patterns and the vegetation structure in temperate forests

Abstract: The aim of the study was to explore the relationship between the functional diversity pattern of soil bacteria and the vegetation diversity and structure in temperate forests (Poland). Pine-dominated forests occur on soils with lower pH, fewer nutrient contents (P, Na, Mg, Mn and K) and higher C/N and C/P ratios than beechdominated forests and mixed broadleaved forest with hornbeam and ash. Both forest type and soil horizon (O and A) strongly influenced bacterial catabolic activity and the number of substrates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…The bacterial preference towards easily degradable C compounds on the studied soils may result from the characteristics of pine-delivered organic matter that dominated in the studied stands. It has been shown that the dominating tree species affect the soil bacterial metabolic profiles (Chodak et al 2015 ; Klimek et al 2016 ), and the preferential use of carboxylic acids by the microbial community was observed in pine soil (Yao et al 2006 ; Chodak et al 2015 ; Klimek et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial preference towards easily degradable C compounds on the studied soils may result from the characteristics of pine-delivered organic matter that dominated in the studied stands. It has been shown that the dominating tree species affect the soil bacterial metabolic profiles (Chodak et al 2015 ; Klimek et al 2016 ), and the preferential use of carboxylic acids by the microbial community was observed in pine soil (Yao et al 2006 ; Chodak et al 2015 ; Klimek et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…ANOSIM is a non-parametric permutation procedure to compare between-groups and within-groups dissimilarities on multivariate data ( Clarke and Green, 1988 ). This procedure calculates an R statistic, wherein R = 0, the grouping of treatments is considered random (i.e., there is no interpretable grouping) and R = 1, if all replicates within groups are more similar to each other than any replicates between the groups ( Klimek et al, 2016 ). The overall or ‘global’ R value was consequently used to express differences as dissimilarity between isolate (BG11, FRh2, J18) and control treatments, and the wounded (W) and non-wounded (N) groups.…”
Section: Methodsmentioning
confidence: 99%
“…One explanation might be that the soil physicochemical properties influence the soil microbial activity [20]. Higher nutrient contents, especially N and P, support a higher microbial biomass and may indirectly facilitate an increase of the soil bacteria [10,52]. Under the same temperature and precipitation of both areas, deciduous broadleaf trees produce more litter quantities and have a more rapid decomposition than coniferous trees, thus resulting in higher nutrient levels of deciduous broadleaf trees compared to soils under coniferous tree species [12].…”
Section: Differences In Soil Microbial Community Characteristics Undementioning
confidence: 99%